KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PELANGGAN PADA TOKO ZEE THRIFT LAMONGAN - Erna Nur Faizah; Adi Lukman Hakim; Rizky Wahyudha Rosiawan (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Customer satisfaction can provide benefits, including the relationship between the company and consumers to come back for repeat purchases, and can also form word of mouth recommendations that are profitable for the company. One of them is the retail business, which is a business of distributing goods and services at the final level, which will be directly enjoyed by consumers. The more competitors, the more companies are required to be able to see every opportunity and develop strategies to be able to provide maximum customer satisfaction. This study aims to determine the effect of customer satisfaction on customer repurchase interest. The population in this study were customers at Zee Thrift Lamongan. The sample in this study were 100 respondents using purposive sampling method. The study used primary data by distributing questionnaires to respondents. The data analysis technique uses descriptive analysis and simple linear regression analysis using software tools used in research is SPSS. The results of this study prove that there is an effect of customer satisfaction on repurchase interest at the Zee Thrift Lamongan store.